SEQUENCE VARIATIONS AND HAPLOTYPIC DIVERSITY IN THE MYOSTATIN GENE OF NIGERIAN CATTLE BREEDS - L. HARUNA, ISHAKU; J. EKEGBU, UGONNA (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2022)
The myostatin gene (MSTN) encodes myostatin protein (MSTN), whose function involves regulating muscle growth and development. Using Polymerase Chain Reaction coupled with Single Strand Conformational Polymorphism analysis with nucleotide sequencing, a total of 161 animals from four different breeds and cross breeds of Nigerian cattle were genotyped at the introns 1 and 2 region, as well as exons 1, 2 and 3. Sixteen SNPs were identified, two (c.374- 796C>T and c.374-762C>T) of which are novel and are reported here. The identification of new as well as previously reported genetic variations in MSTN within this species provides more insight into the polymorphic nature of this gene. Thus, providing an important resource for further studies around genomic selection and breeding.